‘HEY BLOG’ CAN PERSONAL WEBSITE ASSIST L2 STUDENTS’ WILLINGNESS TO DO PEER FEEDBACK? - Puspita, Nurul; Aryanika, Septa (Universitas Muhammadiyah Metro, 2024)
Technology's rapid growth has significantly impacted how lecturers incorporate technology into classroom activities, especially when providing feedback. The students will receive feedback during the revision session. There are many techniques for giving feedback on students' writing. For instance, peer and self-feedback are two techniques for checking students' mistakes. Therefore, this research portrays technology as a medium for implementing peer and self-feedback in students' writing. This research aims to describe the integration of media in giving feedback. The media are blogs and Google Docs. This research also gathered students' perceptions of the use of online media. In this research, the researcher implemented qualitative research. This research was conducted by the fourth-semester students of the essay writing class, English Education Study Program, Uin Raden Intan Lampung. The researcher used documentation, an internet survey, and an observation sheet to gather data. The data from the research is analyzed interactively. The findings highlight the significant benefits of utilizing blogs and Google Docs for reflective writing practices. The implication of this research underscores the importance of integrating online media for peer and self-feedback to enhance students' writing skills effectively. This research contributes valuable insight into leveraging technology for academic improvement and fostering a conducive learning environment.